Stem cell collection after lenalidomide, bortezomib and dexamethasone plus elotuzumab or isatuximab in newly diagnosed multiple myeloma patients: a single centre experience from the GMMG-HD6 and -HD7 trials - Kauer, Joseph; Freundt, Emma Pauline; Schmitt, Anita; Weinhold, Niels; Mai, Elias K.; Müller-Tidow, Carsten; Goldschmidt, Hartmut; Raab, Marc-Steffen; Kriegsmann, Katharina; Sauer, Sandra (BMC cancer, 2023)
While quadruplet induction therapies deepen responses in newly diagnosed multiple myeloma patients, their impact on peripheral blood stem cell (PBSC) collection remains incompletely understood. This analysis aims to evaluate the effects of prolonged lenalidomide induction and isatuximab- or elotuzumab-containing quadruplet induction therapies on PBSC mobilization and collection.